Comparison of Bioproduct Quality from Vermiconversion of Spent Pleurotus sajor-caju Compost and Commercial Livestock Excreta - Azizi, A.B.; Shafiza, M.S.; Noor, Z.M.; Noorlidah Abdullah, (Universiti Kebangsaan Malaysia, 2014)
Vermiconversion study was conducted to compare the use of commercial livestock excreta i.e. cow dung (CD) and goat manure (GM) in the vermiconversion of spent mushroom compost (SMC) utilising red worms i.e. Lumbricus rubellus to obtain good quality compost with high nutrient content. This study was performed for 70 days after 21 days of pre-composting at different ratios of livestock excreta and SMC. The highest multiplication and growth of earthworms in number and biomass was recorded in TE with increment of +296.57 and +484.20%, respectively. Moreover, paired samples t-test indicated a significant difference (p<0.05) in earthworms’ number and biomass. The results for non-mixed substrate showed, CD (TA) bioproduct obtained, contained the highest concentration in exchangeable K (1.98%). However, GM (TD) vermicompost recorded the highest content of total N (1.66%) and available P (0.64%). In conclusion, 50% of GM is recommended in vermiculture as well as producing nutrient enriched bioproduct compared with CD with SMC as bulking agent. Furthermore, heavy metal i.e. Cd, Cr, Pb, Cu and Zn content in bioproduct produced from all treatments were lower compared to compost limits set by USA, European countries and Malaysian Recommended Site Screening Levels for Contaminated Land (SSLs).